Latest Research in Vasculitis Reviewed - Cunningham, Muriel (MD Conference Express, 2014)
The term vasculitis encompasses various inflammatory and autoimmune disorders affecting blood vessels. Recent research in several different types of vasculitis is reviewed in this article.